FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT PERUMAHAN DI INDONESIA - Salsabila Ganthari; Syafri Syafri (Media Ekonomi, 2018)
This study aims to analyze the factors that affect housing loans as seen from four banking groups, the State Bank, Regional Government Banks, Private National Banks, and Foreign Banks and Joint Banks. This study uses quarterly panel data from 2012: 1-2016: 1. Data analysis was performed using multiple linear regression analysis panel data. Houses are an important requirement for all humanity, not only as consumer goods but also investment goods. Banking helps prospective customers by providing a credit facility called Housing Loans. Based on the results of the panel data analysis shows that the level of loans and income per capita have a significant effect on housing loans, while loan to value does not significantly influence housing loans.